Immunosuppressant-Associated Neurotoxicity Responding to Olanzapine. (9th July 2014) - Bourgeois, James A.; Hategan, Ana
Abstract : Immunosuppressants, particularly tacrolimus, can induce neurotoxicity in solid organ transplantation cases. A lower clinical threshold to switch from tacrolimus to another immunosuppressant agent has been a common approach to reverse this neurotoxicity. However, immunosuppressant switch may place the graft at risk, and, in some cases, continuation of the same treatment protocol may be necessary. We report a case of immunosuppressant-associated neurotoxicity with prominent neuropsychiatric manifestation and describe psychiatric intervention with olanzapine that led to clinical improvement while continuing tacrolimus maintenance.